Leprosy scenario in Ahmedabad District (Gujarat) - Deepika Uikey; Rima Joshi; Bela J Shah; Nikhil Verma (Wolters Kluwer Medknow Publications, 2019)
Background: In India, leprosy still continues to be one of the major public health problems and demands a continuous awareness for its eradication. The reduction of the load of infection is the cornerstone of leprosy control. Aims: The aim of the present study was to enumerate the epidemiology of leprosy in the Ahmedabad district of Gujarat. Methods: Three hundred new cases of leprosy (multidrug therapy cases) and patients who had completed antileprosy treatment and developed new signs and symptoms after that during the period from June 2010 to December 2012 were included in the study. A detailed history, clinical examination, and relevant tests were done. Results: Out of a total of 300 patients, male-to-female ratio was 2.1:1. Family history was positive in 4.3% of patients. Lepromatous leprosy was seen in 27.3%, pure neuritic leprosy occurred in 12 (3.9%), and smear positivity was seen in (44.6%). Thirty (10%) patients developed type 1 reaction and 32 (10.6%) patients had type 2 reaction. Nearly 1.3% of the cases were relapsing cases. Limitations: The study had geographical limitation and the study did not cater the whole population but only the cases who reported to the hospital. Hence, the social stigma factor associated with leprosy could not be annulled. Conclusions: Leprosy still prevails and adequate knowledge and clinical skills, sensitive diagnostic tools and proper supply of medicines from the medical end and early reporting of symptoms, compliance regarding medicine intake, and social awareness to null social stigma associated with it from the patient's end may bring the country as a whole to the target of leprosy elimination.